Part I: Electroreductive polymerization of nanoscale solid polymer electrolytes for three-dimensional lithium-ion batteries. Part II: Physical characterization and hydrogen sorption kinetics of solution-synthesized magnesium nanoparticles - Arthur, Timothy Sean, author; Prieto, Amy L. (Amy Lucia), advisor; Bailey, Travis Slade, committee member; Elliott, Cecil Michael, committee member; Shores, Matthew P., committee member; Williams, John D., committee member (Colorado State University. Libraries, 2010)
To view the abstract, please see the full text of the document.
Electroreductive polymerization of nanoscale solid polymer electrolytes for three-dimensional lithium-ion batteries
Physical characterization and hydrogen sorption kinetics of solution-synthesized magnesium nanoparticles
Department Head: Ellen R. Fisher.
Keywords: polymers; nanoparticles; magnesium; hydrogen storage; batteries; Lithium cells -- Materials; Polymerization; Hydrogen as fuel; Conducting polymers